Betalains: Natural plant pigments with potential application in functional foods - Gengatharan, A.; Dykes, Gary; Choo, W. (2015)
Betalains are plant derived natural pigments that are presently gaining popularity for use as natural colorants in the food industry. The growing interest of consumers in the aesthetic, nutritional and safety aspects of food has increased the demand for natural pigments such as betalains to be used as alternative colorants in food products. Although betalains from red beetroot are one of the most widely used food colorant, betalains are not as well studied as compared to other natural pigments such as anthocyanins, carotenoids or chlorophylls. This paper reviews the pharmacological properties, such as antioxidant, anti-cancer, anti-lipidemic and antimicrobial activity of betalains derived from sources such as red beetroot, amaranth, prickly pear and red pitahaya, for potential application as functional foods.